Nuclear magnetic resonance response characteristics and quantitative evaluation method of fluid saturation of lacustrine shale oil - Fan, Ruiqi; Liao, Guangzhi; Mao, Rui; Luo, Xingping; Hou, Lianhua; Zhang, Hao; Tian, Hua; Wang, Gang; Qin, Zhijun; Xiao, Lizhi (Frontiers in Earth Science, 2023)
The quantitative evaluation of fluid saturation is important for formation evaluation of shale oil. However, there is currently no effective method to identify the fluid occurrence state and quantitative evaluate the fluid saturation of lacustrine shale oil because of the complexity of diagenetic minerals and pore types. In this paper, a method is proposed for the quantitative evaluation of fluid saturation based on nuclear magnetic resonance (NMR), X-ray diffraction (XRD) and scanning electron microscopy (SEM) measurements for shale samples of Fengcheng Formation, Mahu sag in Junggar Basin, China. These studies revealed that the shale oil rocks mainly contain quartz, feldspar, dolomite, calcite and clay minerals, both develop organic and inorganic pores. The fluids mainly occur in the form of bitumen, clay bound water, bound water, bound oil and movable oil in this study area. Based on the findings from these experiments, a mixed rock index (MI) was proposed to divided the shale oil formations into three types, including sand shale, dolomitic shale and mudstone. A T1-T2 2D NMR fluid occurrence state characterization map was established to identify the different fluids by the MI and NMR characteristics. The movable oil is well separated from the clay bound water and bitumen signals. Furthermore, a method was proposed to quantitatively calculate the coefficient distribution of bound and movable fluids for shale oil in different formations. Finally, the proposed method was successfully applied into the lacustrine shale oil in the Fengcheng Formation to identify fluid occurrence state and evaluate fluid saturation quantitatively.